Analysis of Indian SARS-CoV-2 Genomes Reveals Prevalence of D614G Mutation in Spike Protein Predicting an Increase in Interaction With TMPRSS2 and Virus Infectivity - Raghav, Sunil; Ghosh, Arup; Turuk, Jyotirmayee; Kumar, Sugandh; Jha, Atimukta; Madhulika, Swati; Priyadarshini, Manasi; Biswas, Viplov K.; Shyamli, P. Sushree; Singh, Bharati; Singh, Neha; Singh, Deepika; et al. (Frontiers in Microbiology, 2020)
COVID-19 caused by SARS-CoV-2 virus emerged as a global pandemic worldwide. In this study, we used ARTIC primers based amplicon sequencing to profile 225 SARS-CoV-2 genomes from India. Phylogenetic analysis identified the presence of all the five reported clades 19A, 19B, 20A, 20B and 20C in the population. The analyses revealed Europe and South-East Asia as two major routes for introduction of the disease in India followed by local transmission. Interestingly, 19B clade was found to be prevalent in our sequenced genomes (17%) as compared to other genomes reported so far from India. Haplotype network analysis showed evolution of 19A and 19B clades in parallel predominantly from Gujarat state in India suggesting it to be one of the major routes of disease transmission in India during the months of March and April, whereas 20B and 20C appeared to evolve from 20A. At the same time, 20A and 20B clades depicted prevalence of four common mutations 241 C>T in 5’UTR, P4715L, F942F along with D614G in the spike protein. D614G mutation has been reported to increase virus shedding and infectivity. Our molecular modeling and docking analysis identified that D614G mutation resulted in enhanced affinity of Spike S1-S2 hinge region with TMPRSS2 protease, possibly the reason for increased shedding of S1 domain in G614 as compared to D614. Moreover, we also observed an increased concordance of G614 mutation with the viral load, as evident from decreased Ct value of spike and ORF1ab gene.